1998
DOI: 10.1002/(sici)1097-4652(199809)176:3<456::aid-jcp2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an early G1 ionic event necessary for cell cycle progression and survival in the MCF-7 human breast carcinoma cell line

Abstract: The mechanism of the G0/G1 arrest and inhibition of proliferation by quinidine, a potassium channel blocker, was investigated in a tissue culture cell line, MCF-7, derived from a human breast carcinoma. The earliest measurable effect of quinidine on the cell cycle was a decrease in the fraction of cells in S phase at 12 hr, followed by the accumulation of cells in G1/G0 phases at 30 hr. Arrest and release of the cell cycle established quinidine as a cell synchronization agent, with a site of arrest in early G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 20 publications
5
63
0
1
Order By: Relevance
“…These biophysical properties are not simply markers but are functional signals; misexpression of an ion transporter induces tumorigenicity in fibroblasts (50), and inhibition of EAG channel function suppresses neoplasm in an animal model in vivo (51). Ion channel function controls the proliferation rate and invasiveness of a number of cell types that often form tumors (49,(52)(53)(54)(55), and overexpression of KCNK9 (strongly overexpressed in breast cancer) promotes tumor formation and confers resistance to hypoxia and serum deprivation (56). Misexpression of KCNE1 did not induce tumors per se.…”
Section: Discussionmentioning
confidence: 99%
“…These biophysical properties are not simply markers but are functional signals; misexpression of an ion transporter induces tumorigenicity in fibroblasts (50), and inhibition of EAG channel function suppresses neoplasm in an animal model in vivo (51). Ion channel function controls the proliferation rate and invasiveness of a number of cell types that often form tumors (49,(52)(53)(54)(55), and overexpression of KCNK9 (strongly overexpressed in breast cancer) promotes tumor formation and confers resistance to hypoxia and serum deprivation (56). Misexpression of KCNE1 did not induce tumors per se.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that clotrimazole or TRAM-34 blocked the IKCa1 current and cell proliferation in HEC-1-A cells are consistent with this explanation. It has been known that cells in the early G 1 phase are depolarized; however, they are hyperpolarized during the progression through G 1 into the S phase (Wang et al, 1998;Ghanshani et al, 2000). Inhibition of K Ăž channels leads to membrane depolarization and cellcycle arrest in early G 1 phase in the MCF-7 human breast carcinoma cell line (Wang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that cells in the early G 1 phase are depolarized; however, they are hyperpolarized during the progression through G 1 into the S phase (Wang et al, 1998;Ghanshani et al, 2000). Inhibition of K Ăž channels leads to membrane depolarization and cellcycle arrest in early G 1 phase in the MCF-7 human breast carcinoma cell line (Wang et al, 1998). Conversely, activation of K Ăž channels promotes the cellcycle progression from the G 0 /G 1 to S phase (Wonderlin et al, 1995;Ouadid-Ahidouch et al, 2001;Chittajallu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with human breast tumor cell lines demonstrated that quinidine (90 M) is an anti-proliferative agent as well. Quinidine arrested cells in early G 1 phase and induced apoptosis by 72-96 h in MCF-7 cells (12), but the biochemical basis for the anti-proliferative effect of quinidine was not well understood. To clarify the molecular mechanisms of the antiproliferative activity of quinidine, we investigated the effects of quinidine on histone acetylation and cell cycle regulatory proteins.…”
Section: Waf1mentioning
confidence: 99%